Preparation of International Business Contracts in Facing the ASEAN Economic Community Era - Sahlan Sahlan (Faculty of Law, Hasanuddin University, 2016)
This article reviews the preparation for composing and formulating the international business contracts in facing the ASEAN Economic Community era. The study used the normative approach by collecting the materials related to the international business contracts. The outcomes of the research indicate that constitutionally, the Indonesian government must provide protection and equitable legal certainty for Indonesian citizens who intend to conduct business transactions within the framework of AEC. Format and writing techniques of international business contracts is compulsory known by the business people and their legal consultants that they do not suffer losses due to errors in the preparing of contract that violates the rules and provisions of international business contract.